2006
DOI: 10.2460/javma.228.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic tests used for detection of bovine viral diarrhea virus and prevalence of subtypes 1a, 1b, and 2a in persistently infected cattle entering a feedlot

Abstract: Rapid tests such as ACE permit identification and segregation of PI cattle pending results of further tests, thus reducing their contact with the rest of the feedlot population. Although vaccines with BVDV1a and 2a components are given to cattle entering feedlots, these vaccines may not provide adequate protection against BVDV1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 23 publications
5
75
1
2
Order By: Relevance
“…The BVDV isolates were typed as BVDV1a, BVDV-1b, BVDV-2a, or BVDV-2b, based on the phylogenetic comparisons of sequences of the 59-untranslated region (UTR) of the viral genome. 7,10,11 Reference BVDV strains were included in these comparisons, including those BVDV strains currently used in viral vaccines. The BVDV IHC testing was performed on formalin-fixed ear notches from 94 cattle in the study.…”
Section: Agent Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The BVDV isolates were typed as BVDV1a, BVDV-1b, BVDV-2a, or BVDV-2b, based on the phylogenetic comparisons of sequences of the 59-untranslated region (UTR) of the viral genome. 7,10,11 Reference BVDV strains were included in these comparisons, including those BVDV strains currently used in viral vaccines. The BVDV IHC testing was performed on formalin-fixed ear notches from 94 cattle in the study.…”
Section: Agent Identificationmentioning
confidence: 99%
“…The BVDV IHC testing was performed on formalin-fixed ear notches from 94 cattle in the study. 7 The IHC procedure was performed at the OADDL as described by using the primary anti-BVDV mAb 3.12 F1. 7 The BRSV and BCoV were assayed in 194 lung homogenates by using gel-based reverse transcription polymerase chain reaction (RT-PCR) assays.…”
Section: Agent Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Further, mortality rates among PI animals are 10-fold higher than those observed in non-PI animals. 5 Skin biopsies, serum, and buffy coat are the sample types most frequently collected for surveillance efforts, and commercial test kits have been developed based on testing of these sample types.…”
mentioning
confidence: 99%
“…In the USA, however, where beef cattle production is the highest in the world, the potential risk of transmission of both BVDV 1 and 2 is reserved for persistently infected (PI) dairy and beef cattle entering the feedlot. A recent study demonstrated that of 21,743 cattle entering the feedlot, 0.4% were PI (Fulton et al 2006). Among cattle herds (dairy and beef) seroprevalence varied between 19% and 89%, but the prevalence of PI animals in the cattle population ranged from 0.5% to 2% (Cowley et al 2012).…”
Section: Introductionmentioning
confidence: 99%